Environmental Archaeology and Heritage in Dakhla Oasis, Egypt - Karin Kindermann; Richard Bussmann (Heritage)
Debates about archaeological heritage in Egypt are commonly focused on the spectacular monuments of the Pharaonic, Greek, and Roman periods. In contrast, landscapes and the long prehistory of Northeast Africa receive far more limited attention. The Cologne Summer School (CSS), ‘Environmental archaeology: dealing with cultural and natural heritage’, organised in Dakhla Oasis (Egypt) in September 2023, brought Egyptian and German students, archaeologists and heritage professionals together to discuss how heritage management, the protection of the landscape and archaeological fieldwork can be integrated meaningfully in the region. This paper summarises the results of the discussions of the summer school, set against an outline of current site-based heritage practises in Egypt and archaeological research in and around Dakhla Oasis. A major outcome of the discussions is the realisation that a distinct narrative needs to be developed for Dakhla Oasis and the surrounding desert landscape to provide an encompassing strategy for the management and protection of its archaeological heritage, from prehistoric times through Pharaonic Egypt to the recent past.